7C Online Marketing Communication Strategies That Affect Noon.com Website Success - Cannel, Chesoh; Bilmanoch, Sasiphan; Dechacheep, Suthep (Siam Communication Review, 2022)
The objectives of this study were 1) to study information exposure behavior for online shopping service via Noon.com website among residents in Jeddah of Saudi Arabia. 2) To study the factors affecting the satisfaction and decision making of online shopping service through Noon.com's 7C online marketing communication strategy in Jeddah residents of Saudi Arabia. 3) To study what has influenced Noon.com's success in using online shopping services.com by in Jeddah residents of Saudi Arabia. 3) To study what has influenced Noon.com's success in using online shopping services in Jeddah residents of Saudi Arabia. It is a quantitative research study from a sample who lived in the city of Jeddah 400 people in Saudi Arabia. By using the method of collecting data with online questionnaires via Google form and statistical processing with SPSS program. The results of the research can be summarized as follows: The demographic characteristics of the sample, which lived in the city of Jeddah Saudi Arabia found that most of them were male. Age between 20-30 years old with a bachelor's degree and most of them work as employees of private companies. Them have an average monthly income of more than 50,000 baht and most of them are of Saudi Arabian citizenship. Noon.com news exposure behavior of Jeddah residents Saudi Arabia found that most of them had information exposure 5-6 times/week with a period of access to the website more than 60 minutes/day and most of them are accessed during the period of 8:01-12:00 p.m.. It was also found that food/snack products were the most popular when users shop online through Noon.com buying more than 1,000 baht/time and most users access the Noon.com website via mobile phone or smartphone. Factors affecting Jeddah residents satisfaction and decision making through Noon.com's 7C marketing communication strategy Saudi Arabia. It was found that the average level of satisfaction affecting the decision to use the online shopping service via Noon.com website in terms of context, beautiful color design was 4.78. In terms of website content with information being updated and updated always equals 4.75. The social aspect which was written through a web forum was 4.76. The response to the personal needs of users who were able to recommend changes to this website was 4.76. The communication aspect, which was able to contact the company in many ways, was 4.72. In terms of commercial businesses that use this website to always trade, it is equal to 4.82. The link that the user receives a quick response from the company is 4.69. By the satisfaction and decision to use the online shopping service through the Noon.com as a whole has an average of 4.70. What made Noon.com successful in the first two places with the same average of 4.75 is that when users want to buy products, they think of Noon.com. Even if there is a website to buy new products online as a market share the users still use the service through the Noon.com website and the users will not try to switch to another website if they are still satisfied with the Noon.com website equal to 4.74.